The Inca neighborhoods of 16th-Century Cusco in the chronicles of Inca Garcilaso de la Vega: A toponymic study - Tord Velasco, Lorena (2024)
This article presents the initial findings of a toponymy study based on the chronicles of Inca Garcilaso de la Vega concerning the Inca neighborhoods of the city of Cusco. Garcilaso recorded twenty names of Inca neighborhoods that, according to the chronicler, were still in use during his residence in Cusco between 1539 and 1560. The documentation of these names has enabled us to conduct a thorough search in the historical archives of Cusco, Lima and Seville. Based on these results, we can assert that these names did indeed exist and remained in use among the residents of Cusco throughout the entire Viceroyalty period.